5PSQ-054 Assessement of occupational practices: analysis of the prescriptions of transcatheter aorticvalve implantation (tavi). Issue 1 (23rd March 2023) - Fouillet, J; Prisque, N; Faure, C; Perrey, J
Abstract : Background and Importance: Transcatheter implantation of an aortic bioprosthesis (TAVI) allows the replacement of the aortic valve by a prosthesis without open surgery. Like any medical device, the implantation of these prostheses must comply with the CE mark. As the funding of TAVIs is under specifics criteria, those must also be respected. Aim and Objectives: To carry out an overview of the compliance of the TAVI prescriptions with the funding criteria (FC). Material and Methods: 33 patients were randomly selected from the 300 TAVIs implanted in 2021. Valve models, implantation routes, and patient data were extracted from the internal traceability software (GILDAS) at the university hospital and from computerised medical records (DxCare). These data were analysed with a grid developed from the FC. Results: Among the 33 patients selected, 15 were men et 18 were women, ranging in age from 68 to 94 years, with an average age of 80.1 years. 84.8% (n=28) of the valves were placed transfemorally, 6.1% (n=2) transapically and 9.1% (n=3) transcarotidly. 28 patients had symptomatic severe aortic stenosis (ASN), 1 patient had asymptomatic ASN, and 4 patients had cardiac decompensation on ASN. Contraindications to surgery were documented in the patient record in 84.8% (n=28) of cases. The Society of Thoracic Surgeons (STS) database score was specified in 42.4% (n=14) of the cases and the Euroscore was not specified for any patient. Multidisciplinary consultations were carried out in 100% of cases, as well as pre- and post-TAVI assessments. A total of 24 non-compliances (NC) were observed, including 16 patients with 1 NC and 4 patients with 2 NC. The funding criteria were not respected in 27.3% (n=9) of cases. Conclusion and Relevance: Although most of the patient files stipulate comorbidities consistent with the placement of a TAVI, there is still a lack of formalisation of the indications: the STS score is mentioned in only 42.4% of the cases, even though it is part of the FC. A report was presented to the recruiting physicians and the importance of transcribing the STS score in the patient file was explained. References and/or Acknowledgements: Conflict of Interest: No conflict of interest